The Use of Bandura in Modern Art Projects: Revival of Traditions in the Modern World - Buchkivska, Galyna; Kachurynets, Serhii; Tsyhaniuk, Liutsiia (Pedagogical Discourse, 2024)
The article analyzes the historical and socio and political conditions of the emergence and development of bandura art in Ukraine, characterizes the main principles of the academicization of bandura performance, which began at the beginning of the 20th century and is connected with the activities of an outstanding Ukrainian figure, composer, writer, engineer, kobzar and designer of bandura Hnat Khotkevych and his followers. The review of the process of bringing the bandura art beyond the boundaries of the authentic Kobzar tradition, the introduction of the professionalization of bandura performance at various levels of education, the improvement of the bandura design, which had a significant impact on the change in the historical and social functions of this instrument at the turn of the 20th and 21st centuries, is carried out, the consequences of the Soviet intervention in the development of Ukrainian culture and the process of replacing the authentic content of bandura performance with a pseudo-bandura performance, which in modern studies has received the definition of a simulacrum of bandura art, are analyzed. The research examines the use of the bandura in artistic projects in the 21st century, which involves the application of knowledge about the methods of sounding the instrument, working with a microphone, stage image, choosing a location for a performance, public relations, promotion, etc. It is noted that bandura is used in related art forms, such as choreography, which promotes a deep emotional connection between a sound and movement, and in theatrical performances, where bandura becomes an important element of scenography and dramaturgy. The important idea of this article is that despite the long-term oppression and extermination of kobzarism by the Soviet government, its attempt to distort the deep essence of bandura art in Ukraine, it survived and regained both its authentic beauty and acquired other various artistic forms.